Cloud Powered Deep Learning-Emerging Trends - Jagirdar, Srinivas; Venkata Subba Reddy, K; Qyser, Ahmed Abdul Moiz (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is making inroads into other areas of research. Advanced research area like Deep Learning is now not limited to just huge organizations. Cloud Computing is making it easy for even small researchers to have a go at Deep Learning. One needs to just harness the unlimited Computing power the Cloud offers. This paper presents a review of Deep Learning, opportunities & Challenges of Deep Learning .The paper also throws light on the role of Cloud Computing in Deep Learning.